Association of Veterinary Hematology and Transfusion Medicine (AVHTM) Transfusion Reaction Small Animal Consensus Statement (TRACS). Part 1: Definitions and clinical signs. Issue 2 (31st March 2021) - Davidow, Elizabeth B.; Blois, Shauna L.; Goy‐Thollot, Isabelle; Harris, Lauren; Humm, Karen; Musulin, Sarah; Nash, Katherine J; Odunayo, Adesola; Sharp, Claire R.; Spada, Eva; Thomason, John; Walton, Jenny; et al.
Abstract: Objective: To use a systematic, evidence‐based consensus process to develop definitions for transfusion reactions in dogs and cats. Design: Evidence evaluation of the literature was carried out for identified transfusion reaction types in dogs and cats. Reaction definitions were generated based on synthesis of human and veterinary literature. Consensus on the definitions was achieved through Delphi‐style surveys. Draft recommendations were made available through industry specialty listservs and comments were incorporated. Results: Definitions with imputability criteria were developed for 14 types of transfusion reactions. Conclusions: The evidence review and consensus process resulted in definitions that can be used to facilitate future veterinary transfusion reaction research.